Sustainable farming genes: spatial distribution and influencing factors of Chinese Agricultural Heritage Sites (CAHSs) - Li, Chang; Tong, Tong; Huang, Xiaohui (Frontiers in Sustainable Food Systems, 2023)
Agricultural heritage is one of the socio-ecological production landscapes which inherits regional agricultural genes. It is an essential part of cultural heritage and has become an emerging field of research. Previous studies have focused on the value evaluation and sustainable mechanism of sites identified on the list of global and national agricultural heritage; however, the description of the distribution pattern and influencing factors, as well as the potential agricultural heritages have been ignored. The present study aims to reveal the spatial distribution and change of the Chinese Agricultural Heritage Site (CAHS) through spatial analysis. The results show that: (1) The distribution of 532 CAHSs (7 types) is uneven, and the horticulture system gains the quantitative edge (55.26%); (2) The distribution of CAHSs shows the spatial aggregation of "dense in the east and sparse in the west". Beijing, Shandong, Zhejiang, and their surrounding areas form the densest belt area of heritages, and 44.17% of the CAHSs are distributed in this belt;(3) Single factor analysis shows that culture, population, soil, and elevation are the most critical driving forces which affect the distribution (all explanatory power >0.20). Two factors interaction analysis confirms that the distribution is influenced by the enhancement of both natural and human factors. Among them, high explanatory power (>0.70) is related to the pairing between culture factors, population factors, and geographic factors (i.e., elevation, soil, and river). This study could provide scientific evidence for the assessment, protection, and sustainable development of CAHS.